Multimodal Metaphor in Ten Dutch TV Commercials - Forceville, Charles (Public Journal of Semiotics, 2007)
Since the publication of Lakoff and Johnson’s Metaphors We Live By (1980), conceptual metaphor theory (CMT) has dominated metaphor studies. While one of the central tenets of that monograph is that metaphors are primarily a phenomenon of thought, not of language, conceptual metaphors have until recently been studied almost exclusively via verbal expressions. Another limitation of the CMT paradigm is that it has tended to focus on deeply embedded metaphors rather than on creative metaphors of the kind that Black (1979) discusses. One result of this focus is that relatively little attention is paid in CMT to the form and appearance a metaphor can assume (cf. Lakoff and Turner 1989). Clearly, which channel(s) of information (language, visuals, sound, gestures, among others) are chosen to convey a metaphor is a central factor in how a metaphor is construed and interpreted. A healthy theory of metaphor as a structuring element of thought therefore requires systematic examination of both its multimodal and its creative manifestations. Conversely, research into non-verbal and multimodal metaphor can help the theorization of multimodality. In this paper it is shown that creative metaphors occurring in commercials usually draw on a combination of language, pictures, and non-verbal sound. After an inventory of parameters involved in the analysis of multimodal metaphors, ten cases are discussed, with specific attention to the role of the various modes in the metaphors’ construal and interpretation. On the basis of the case studies, the last sections of the paper discuss three issues that are crucial for further study: (1) the ways in which similarity is cued in multimodal, as opposed to verbal, metaphors; (2) the problems adhering to the verbalization of multimodal metaphors; (3) the influence of textual genre on the interpretation of multimodal metaphors.